Quaid-e-azam ney farmaya - Riaz Fehmeeda (Oxford University Press; Lahore, 2012)
"Quaid-e-Azam Ney Farmaya" compiles the visionary speeches and statements of Muhammad Ali Jinnah, reflecting his wisdom, leadership, and commitment to the ideals of Pakistan's creation and its future progress.